Vertical-cavity surface-emitting laser (VCSEL)-based ultrafast photonic sintering of solid oxide fuel cells (SOFCs): prospects for time-efficient/two-dimensional scalability to large-sized SOFCs. Issue 17 (13th April 2023) - Kim, Jaehwan; Rehman, Saeed Ur; Lee, Myeong-Ill; Hussain, Amjad; Noh, Youngsu; Oh, Jiwon; Ku, Wonseck; Kwak, Na-Eui; Kim, Do-Hyeong; Hwang, Heesu; Yoon, Hee-Sung; Park, Seungho; et al.
Abstract : 980 nm VCSEL illumination eliminates the organic additives and densifies the laminated multilayered SOFC NiO–YSZ|NiO–ScCeSZ|ScCeSZ|GDC|GDCscaffold in just 2.42 h compared to >100 h needed for the conventional thermal sintering process. Abstract : Solid oxide fuel cells (SOFCs) are potential future energy conversion devices. Here, we report infrared vertical-cavity surface-emitting lasers (VCSELs) for the ultrafast fabrication of SOFCs. VCSELs eliminate the organic additives and densify the laminated multilayered SOFC NiO–YSZ|NiO–ScCeSZ|ScCeSZ|GDC (where YSZ, ScCeSZ, and GDC denote Zr0.92 Y0.08 O2− δ, Zr0.89 Sc0.1 Ce0.01 O2− δ, and Ce0.9 Gd0.1 O2− δ, respectively) in just 2.42 h compared to >100 h needed for the conventional thermal sintering process. The process benefits from a VCSEL-based infrared light-material coupling effect, which allows a rapid and uniform thermal heating profile. LSC (La0.6 Sr0.4 CoO3− δ )–GDC composite cathodes and GDC scaffolds for LSC infiltration are also fabricated using VCSEL-based sintering. SOFCs fabricated using VCSELs alone and in combination with infiltrated LSC generated 1.86 and 2.24 W cm −2 at 750 °C, respectively, and performed more robustly compared to the 1.69 W cm −2 and degradative performance of the SOFC fabricated using conventional sintering. VCSELs offer excellent processing compatibility and show great potential for accelerated fabrication of high-performance SOFCs.